Positive electrode active material, preparation method thereof, positive electrode plate and application of positive electrode plate
By controlling the mixing and sintering conditions of the lithium source and precursor during the sintering process of the lithium-ion battery positive electrode material, and using specific particle size ranges and theoretical relationships, the problem of low production capacity of the lithium-ion battery positive electrode material is solved, and the consistency of the performance and capacity of the positive electrode active material is achieved.
Patent Information
- Application Number
- CN202411782917.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-03-11
AI Technical Summary
During the sintering process, the positive electrode materials of the existing lithium-ion battery are too small, resulting in low loose density and low production capacity. When the lithium OH·H2O particle size is increased to increase production capacity, the performance of the positive electrode active material will decline.
By uniformly mixing the lithium source and the precursor in the cassette and performing sintering treatment within a specific particle size range, the theoretical relationship between the average particle size (D50) x of the specific lithium source, the loose density (y) of the mixed raw materials, and the amount of the cassette (z) per unit volume, is used to achieve consistency of the performance and improvement of the production capacity of the cathode active material.
On the basis of ensuring the performance of the positive electrode active material, the production capacity of the positive electrode active material is improved, the cost of inquiry and experimental is reduced, the production efficiency is improved, and the correspondence between the optimal particle size range of the lithium source and the amount of the sams per unit volume is positioned.
Smart Images

Figure CN119591172A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery technology, and specifically, to positive electrode active materials and preparation methods thereof, positive electrode sheets and applications thereof, and further to positive electrode active materials and preparation methods thereof, positive electrode sheets, lithium-ion batteries and electrical equipment. Background Art
[0002] The rapid development of technology is inevitably accompanied by huge energy consumption, so excellent energy storage equipment plays a vital role. For this reason, people are constantly innovating in the research of energy storage equipment, such as solar cells that convert solar energy into electrical energy, new supercapacitors, sodium ion batteries, etc. Among the many energy storage devices, lithium-ion batteries have become the best energy storage device at present due to their advantages such as long cycle life, high specific capacity, high energy density, and low self-discharge.
[0003] In the development process of lithium-ion batteries, in order to obtain higher energy and power density, and to stably increase battery voltage and capacity, the optimization and development of positive electrode active materials has become the best way to improve the performance of lithium-ion batteries. At the same time, positive electrode active materials account for the highest cost in the production process of lithium-ion batteries, so in order to obtain a process route with high performance and production capacity of positive electrode active materials, it is necessary to fully explore the positive electrode materials from raw materials to process conditions.
[0004] Lithium-ion battery ternary or multi-element cathode materials are generally obtained by sintering mixed precursors, lithium sources, etc. In the current commercial cathode material sintering process, in order to make the lithium source and the precursor physically and mechanically mixed evenly to ensure the reaction uniformity during the solid phase sintering process, the existing process will use a lithium source with a very small particle size. However, the smaller the lithium source particle size, the fluffier it is, the lower the bulk density, and the less loading during the sintering process. Although increasing the LiOH particle size can effectively increase the bulk density (AD) of the material and the sintering loading of the cathode active material, and ultimately increase the single batch output of the cathode material, the increase in the LiOH·H2O particle size will cause the performance of the cathode active material to decline. How to improve the production capacity of the cathode active material while ensuring the performance of the cathode active material has become a problem in the actual production of cathode materials for lithium-ion batteries. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art at least to some extent. To this end, one object of the present invention is to provide a method for preparing a positive electrode active material, which can achieve the consistency of the performance of the positive electrode active material prepared under a specific LiOH particle size range.
[0006] In one aspect of the present invention, the present invention provides a method for preparing a positive electrode active material. According to an embodiment of the present invention, the method for preparing a positive electrode active material comprises: uniformly mixing a lithium source and a precursor to obtain a mixed raw material, and placing the mixed raw material in a sagger, wherein the bulk density of the precursor is 1.7 g / cm 3 -2.1g / cm 3 ; Sintering the mixed raw material to obtain the positive electrode active material, wherein the average particle size of the lithium source (D50) x ( μ m), the bulk density y (g / cm 3 ), unit volume of sagger filling amount z (kg / dm 3 ) satisfies the following formula (1) and formula (2),
[0007]
[0008] y=0.77+0.12ln(x-12.28) formula (2).
[0009] According to an embodiment of the present invention, the average particle size (D50) x of the lithium source, the loose density (AD) y of the mixed raw material, and the amount of the sagger per unit volume z satisfy the above-mentioned theoretical relationship, which can facilitate intuitively obtaining the theoretical production capacity of the positive electrode active material at different lithium source particle sizes during the production process of the positive electrode active material, reduce exploratory experiments, and reduce time and experimental costs; moreover, it is helpful to achieve the consistency of the performance of the positive electrode material prepared within a specific lithium source particle size range; it is helpful to locate the corresponding relationship between the optimal particle size range of the lithium source and the amount of the sagger per unit volume in the production process; moreover, the positive electrode active material obtained by the above-mentioned relationship has good electrochemical properties, which can effectively improve production efficiency.
[0010] According to an embodiment of the present invention, the lithium source is LiOH·H2O, and the average particle size D50 of the lithium source is 13.5 μm-50 μm.
[0011] According to an embodiment of the present invention, the loading height of the sagger is 55%-75% of the height of the sagger.
[0012] According to an embodiment of the present invention, the height of the sagger is 135 mm-165 mm, and the loading height of the sagger is 90 mm-100 mm.
[0013] According to an embodiment of the present invention, the precursor is NieCobMncRd(OH)2, R is a doping element, the doping element is one or more of Al, Zr, Y, Mg, and W, 0.6≤e≤1.0, 0.0≤b≤0.3, 0.0≤c≤0.3, 0.0≤d≤0.3, and 0.95≤e+b+c+d≤1.05.
[0014] According to an embodiment of the present invention, the method for preparing a positive electrode active material also satisfies at least one of the following conditions: the molar ratio of the lithium source to the precursor is 1.0 to 1.05; the mixed raw material also includes an additive; the temperature of the sintering treatment is 650°C-850°C, and the time is 6h-10h; the pressure of the sintering treatment is less than or equal to 20Pa; the oxygen concentration in the sintering treatment is ≥90%.
[0015] According to an embodiment of the present invention, the bulk density of the mixed raw materials in the sagger is greater than or equal to 0.81 g / cm 3 The amount of sagger per unit volume is greater than or equal to 0.75 kg / dm 3 .
[0016] In another aspect of the present invention, the present invention provides a positive electrode active material. According to an embodiment of the present invention, the positive electrode active material includes one prepared by the method described above. As a result, the electrochemical performance of the positive electrode active material is better, and the overall performance of the lithium-ion battery can be effectively improved; the production efficiency and production capacity are high. It can be understood by those skilled in the art that the positive electrode active material has all the characteristics and advantages of the method for preparing the positive electrode active material described above, and no further elaboration is given here.
[0017] In another aspect of the present invention, the present invention provides a positive electrode plate. According to an embodiment of the present invention, the positive electrode plate includes the positive electrode active material described above. Thus, the positive electrode plate has good electrochemical properties and helps to improve the overall performance of the lithium-ion battery.
[0018] In another aspect of the present invention, the present invention provides a lithium ion battery. According to an embodiment of the present invention, the lithium ion battery comprises the positive electrode sheet described above. Thus, the lithium ion battery has good electrical properties such as specific capacity and cycle capacity retention rate.
[0019] In another aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device comprises the lithium-ion battery described above, so that the electric device has good performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0021] Figure 1 is the XRD spectrum of the positive electrode active material obtained in Examples 1 to 4;
[0022] Figure 2 is a comparison of electron microscope scanning images of the positive electrode active material obtained in Example 1 at different magnifications;
[0023] Figure 3 is a comparison of electron microscope scanning images of the positive electrode active material obtained in Example 2 at different magnifications;
[0024] Figure 4 is a comparison of electron microscope scanning at different magnifications of the positive electrode active material obtained in Example 3;
[0025] Figure 5 is a comparison of electron microscope scanning images of the positive electrode active material obtained in Example 4 at different magnifications;
[0026] Figure 6 is a scanning electron microscope image of the positive electrode active material obtained in Example 6;
[0027] Figure 7 is a scanning electron microscope image of the positive electrode active material obtained in Example 7;
[0028] Figure 8 is a scanning electron microscope image of the positive electrode active material obtained in Example 8;
[0029] Fig. 9 is a scanning electron microscope image of the positive electrode active material obtained in Example 9;
[0030] Fig.10 is a scanning electron microscope image of the positive electrode active material obtained in Example 10;
[0031] Fig.11 This is a scanning electron microscope image of the positive electrode active material obtained in Example 11. DETAILED DESCRIPTION
[0032] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0033] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.
[0034] Ternary or multi-element positive electrode materials for lithium-ion batteries are generally obtained by sintering mixed precursors, lithium sources, etc. At present, in the sintering process of positive electrode materials, in order to make the lithium source and the precursor physically and mechanically mixed evenly to ensure the reaction uniformity during the solid phase sintering process, the existing process will use a lithium source with a very small particle size. However, the smaller the particle size of the lithium source, the fluffier it is, the lower the loose density, and the less loading during the sintering process, resulting in a low production capacity of the positive electrode active material. Based on the above problems, the present invention proposes a method for preparing a positive electrode active material, which can select a suitable lithium source on a conventional production line to accurately control the production capacity of the positive electrode active material.
[0035] Based on this, in one aspect of the present invention, the present invention provides a method for preparing a positive electrode active material. According to an embodiment of the present invention, the method for preparing a positive electrode active material comprises:
[0036] S100: The lithium source and the precursor are uniformly mixed to obtain a mixed raw material, and the mixed raw material is placed in a sagger, wherein the bulk density of the precursor is 1.7 g / cm 3 -2.1g / cm 3 .
[0037] In some embodiments of the present invention, the average particle size (D50) x ( μ m) Bulk density of mixed raw materials y (g / cm 3 ), unit volume of sagger filling amount z (kg / dm 3 ) satisfies the following formula (1) and formula (2),
[0038]
[0039] y=0.77+0.12ln(-12.28) formula (2).
[0040] Through the above formula, the correspondence between the average particle size D50 of the lithium source, the loose density of the mixed raw material, and the amount of the sagger per unit volume can be determined, and then the corresponding average particle size D50 of the lithium source, the loose density of the mixed raw material, and the amount of the sagger per unit volume during charging can be set, that is, the loose density of the mixed raw material can be obtained by the amount of the sagger per unit volume during production, so as to further obtain the average particle size D50 of the lithium source, or vice versa, the loose density of the mixed raw material can be obtained by the average particle size D50 of the lithium source, so as to further obtain the amount of the sagger per unit volume. In this way, it is convenient to intuitively obtain the theoretical production capacity of the positive electrode active material under different lithium source particle sizes during the production process of the positive electrode active material, reduce exploratory experiments, and reduce time and experimental costs.
[0041] In the embodiment of the present invention, when the above relationship is applied, the bulk density of the precursor is 1.7 g / cm 3 -2.1g / cm 3 , for example, 1.7 g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 In this way, the deviation between the unit volume sagger filling amount of the mixed raw material and the unit volume sagger filling amount calculated according to the formula after adding the mixed raw material into the sagger is small, which has better guiding significance; if the bulk density of the precursor is less than 1.7g / cm 3 , or greater than 2.1g / cm 3 The deviation between the unit volume of the mixed raw material and the unit volume of the sagger after adding the mixed raw material into the sagger calculated by the formula is greater than 0.04, which has no guiding significance in the production process. In some specific embodiments, the bulk density of the precursor is 1.7 g / cm 3 -1.95g / cm 3 In some more specific embodiments, the bulk density of the precursor is 1.9 g / cm 3 .
[0042] According to some embodiments of the present invention, the precursor is Ni e Co b Mn c R d (OH)2, is a polycrystalline particle, R is a doping element, the doping element is one or more of Al, Zr, Y, Mg, W, 0.6≤e≤1.0, 0.0≤b≤0.3, 0.0≤c≤0.3, 0.0≤d≤0.3, 0.95≤e+b+c+d≤1.05. In some specific embodiments, the above precursor can be a precursor of a high-nickel ternary positive electrode active material, such as Ni 0.88 Co 0.09 Mn 0.03 (OH)2、Ni 0.904 Co 0.059 Mn 0.037 (OH)2, thus, the above formulas (1) and (2) are more applicable, and thus high nickel positive electrode active materials such as LiNi can be prepared. 0.88 Co 0.09 Mn 0.03 O2、LiNi 0.904 Co 0.059 Mn 0.037Furthermore, in some embodiments, the doping of R elements can further improve the electrochemical properties and crystallization properties of the prepared positive electrode active material.
[0043] According to some embodiments of the present invention, the loading height of the sagger is 55%-75% of the height of the sagger, for example, the loading height of the sagger is 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, etc. of the height of the sagger. In this way, the above-mentioned loading requirements can make the mixed raw materials in the sagger fully and evenly heated, improve the yield of the positive electrode active material, and reduce the amount of residual alkali on the surface of the positive electrode active material, and can also effectively ensure that the mixed raw materials are heated and exhausted well during the sintering process; if the loading height in the sagger is too low, the production capacity will be relatively reduced; if the loading height in the sagger is too high, it is easy to make the mixed raw materials unevenly heated, which will lead to a high residual alkali content, which is not conducive to improving the electrochemical properties of the positive electrode active material. In some specific embodiments, the filling height of the sagger is 60%-67% of the height of the sagger; in other specific embodiments, the filling height of the sagger is 64%-65% of the height of the sagger.
[0044] According to some embodiments of the present invention, the height of the sagger is 135mm-165mm, and the loading height of the sagger is 90mm-100mm. In this way, the mixed raw materials in the sagger can be fully and evenly heated according to the above loading requirements, thereby improving the yield of the positive electrode active material and reducing the amount of residual alkali on the surface of the positive electrode active material.
[0045] In some specific embodiments, the sagger is made of zirconium oxide. In some specific embodiments, the size of the sagger is (330±15)*(330±15)*(150±15)mm 3 (length*width*height), the height of the sagger mixture is 97mm.
[0046] According to some embodiments of the present invention, the lithium source is LiOH·H2O, and the average particle size D50 of the lithium source is 13.5μm-50μm, for example, 13.5μm, 15μm, 16μm, 18μm, 20μm, 23μm, 25μm, 28μm, 30μm, 33μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm, and 50μm. The lithium hydroxide of the above particle size can effectively obtain a higher bulk density and a unit volume of the sagger, thereby increasing the production capacity of the positive electrode active material; moreover, it can also help to improve the uniformity of the subsequent mixed raw material sintering reaction, so as to obtain a positive electrode active material with stable performance, no obvious difference in structure and surface morphology; further, due to the uniformity of the sintering reaction, it can help to keep the residual alkali on the surface of the positive electrode active material relatively stable, and there will be no major problems, so the electrochemical properties of the positive electrode active material prepared within the above particle size range are relatively similar, thereby ensuring the stability of the performance of the products produced in the same batch. Among them, if the average particle size D50 of the lithium source is less than 13.5μm, the lithium source is relatively fluffy, which is not conducive to increasing the output of the positive electrode active material; if the average particle size of the lithium source is greater than 50μm, the surface residual alkali of the obtained positive electrode active material will be relatively greatly increased, thereby resulting in a decrease in the electrical performance of the product. In some specific embodiments, the average particle size D50 of LiOH·H2O can be 20μm-25μm.
[0047] In the embodiment of the present invention, the test method of the average particle size D50 of the lithium source is: using a particle size analyzer (Mastersizer 3000) for testing, and the test principle is Mie theory. The specific operation is: take a flat spoon of lithium source sample and add it to the dry sampler, cover the sampler cover, select the corresponding test SOP in the software, click to start the test, the instrument starts to initialize, test the background and sample particle size distribution, and the software displays the particle size distribution result after the test.
[0048] In some embodiments of the present invention, in order to further improve production efficiency and reduce costs in the preparation process, a crude lithium source may be used, and then the lithium source of the desired particle size may be obtained by crushing and screening. The specific crushing method includes but is not limited to a mechanical grinding method.
[0049] In some embodiments of the present invention, the bulk density of the mixed raw materials in the sagger is greater than or equal to 0.81 g / cm 3 , for example, 0.81 g / cm 3 , 0.82g / cm 3 , 0.84g / cm 3 , 0.85g / cm 3 , 0.86g / cm 3 , 0.87g / cm3 , 0.88g / cm 3 , 0.9g / cm 3 、0.91g / cm 3 、0.92g / cm 3 , 0.93g / cm 3 , 0.95g / cm 3 、0.98kg / dm 3 , 1.03kg / dm 3 , 1.10kg / dm 3 , 1.21kg / dm 3 , 1.35kg / dm 3 , 1.47kg / dm 3 etc., and / or, the amount of sagger per unit volume is greater than or equal to 0.75kg / dm 3 , for example 0.75kg / dm 3 、0.76kg / dm 3 、0.77kg / dm 3 、0.78kg / dm 3 、0.79kg / dm 3 、0.80kg / dm 3 、0.81kg / dm 3 、0.82kg / dm 3 、0.83kg / dm 3 、0.84kg / dm 3 、0.85kg / dm 3 、0.86kg / dm 3 、0.87kg / dm 3 、0.88kg / dm 3 、0.89kg / dm 3 、0.90kg / dm 3 、0.91kg / dm 3 、0.92kg / dm 3 、0.93kg / dm 3 、0.94kg / dm 3 、0.95kg / dm 3 , 1.060kg / dm 3 , 1.192kg / dm 3 , 1.382kg / dm 3 , 1.440kg / dm 3 Etc., for example. It can be seen that the method of the present invention can obtain a positive electrode active material with a higher yield.
[0050] According to some embodiments of the present invention, the molar ratio of lithium source to precursor is 1.0-1.05, such as 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, etc. This is conducive to obtaining a positive electrode active material with low residual alkali content and good electrochemical performance.
[0051] According to some embodiments of the present invention, the mixed raw material also includes additives. In some specific embodiments, the additives include one or more of oxides, acids, and organic substances of non-metallic elements such as boron, fluorine, silicon, phosphorus, and sulfur, and / or one or more of oxides, salts, hydroxides, or organic substances of metal elements such as aluminum, strontium, magnesium, zirconium, iron, zinc, niobium, tin, titanium, tungsten, and yttrium. In this way, the addition of additives can form a positive electrode active material with a coating layer, and the use of the above-mentioned additives can protect and isolate the positive electrode active material. In addition, the coating layer of the above-mentioned limiting elements can also reduce the formation of residual alkali on the surface of high-nickel positive electrode active materials (nickel molar content is greater than or equal to 0.8). At the same time, different elements as additives also have different characteristics. For example, when the additive selects aluminum, the cycle stability performance of the positive electrode material can be improved.
[0052] S200: placing the mixed raw material into a sagger for sintering to obtain the positive electrode active material.
[0053] According to some embodiments of the present invention, the sintering temperature is 650°C-850°C, such as 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C, 820°C, 850°C, etc., and the time is 6h-10h, such as 6h, 7h, 8h, 9h, 10h, etc., so that the mixed raw materials can be effectively reacted, which is conducive to improving the uniformity of the reaction of the lithium source and the precursor during the solid phase sintering process, so that the surface of the precursor is effectively lithiated to the greatest extent, and it is helpful to reduce the generation of residual alkali. In some specific embodiments, the sintering temperature is 750°C and the sintering time is 8h.
[0054] According to some embodiments of the present invention, the pressure of the sintering treatment (i.e., the pressure inside the furnace of the sintering treatment) is less than or equal to 20Pa, such as 20Pa, 19Pa, 18Pa, 17Pa, 16Pa, 15Pa, 14Pa, 13Pa, 12Pa, 11Pa, 10Pa, etc. This pressure is particularly suitable for the preparation of high-nickel positive electrode materials. Under the above-mentioned pressure atmosphere, the lithium source and the precursor can fully react, improve the efficiency of the sintering reaction, and help reduce the generation of residual alkali. In some specific embodiments, the pressure of the sintering treatment is 8Pa-15Pa; in other specific embodiments, the pressure of the sintering treatment is 10Pa. Among them, when the gas pressure in the furnace is too low, it will cause the gas outside the furnace to flow back, resulting in a relatively high CO2 concentration in the furnace; when the pressure in the furnace is too high, under the condition of a certain air intake, it means that the exhaust effect is relatively poor, and the exhaust gas in the furnace accumulates excessively, which will relatively increase the residual alkali content on the surface of the high-nickel positive electrode material.
[0055] According to some embodiments of the present invention, the oxygen concentration in the furnace during the sintering process is ≥90%, such as 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, etc. In the above-mentioned oxygen atmosphere, the lithium source and the precursor can fully react, the efficiency of the sintering reaction is improved, and it is helpful to reduce the generation of residual alkali. In some specific embodiments, the oxygen concentration in the furnace during the sintering process is 93%.
[0056] According to an embodiment of the present invention, the above-mentioned preparation method and the average particle size (D50) x of the lithium source, the loose density (AD) y of the mixed raw materials, and the amount of potting per unit volume z satisfy the above-mentioned theoretical relationship, which can facilitate the intuitive acquisition of the theoretical production capacity of the positive electrode active material under different lithium source particle sizes during the production process of the positive electrode active material, reduce exploratory experiments, and reduce time and experimental costs; moreover, it is helpful to achieve the consistency of the performance of the positive electrode material prepared under a specific lithium source particle size range; it is helpful to locate the corresponding relationship between the optimal particle size range of the lithium source and the amount of potting per unit volume in the production process; moreover, the positive electrode active material obtained by the above-mentioned relationship has good electrochemical properties, which can effectively improve production efficiency.
[0057] In another aspect of the present invention, the present invention provides a positive electrode active material. According to an embodiment of the present invention, the positive electrode active material includes one prepared by the method described above. As a result, the electrochemical performance of the positive electrode active material is better, and the overall performance of the lithium-ion battery can be effectively improved; the production efficiency and production capacity are high. It can be understood by those skilled in the art that the positive electrode active material has all the characteristics and advantages of the method for preparing the positive electrode active material described above, and no further elaboration is given here.
[0058] According to some embodiments of the present invention, the above-mentioned positive electrode active material can be a high-nickel ternary positive electrode active material, such as LiNi 0.88 Co 0.09 Mn 0.03 O2 and / or LiNi 0.904 Co 0.059 Mn 0.037 O2.
[0059] In another aspect of the present invention, the present invention provides a positive electrode plate. According to an embodiment of the present invention, the positive electrode plate includes the positive electrode active material described above. Thus, the positive electrode plate has good electrochemical properties and helps to improve the overall performance of the lithium-ion battery.
[0060] According to an embodiment of the present invention, in addition to the above-mentioned positive electrode active material, the positive electrode plate further includes a conductive agent and a binder. In some embodiments, the conductive agent includes but is not limited to at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers; in other embodiments, the binder includes but is not limited to at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin.
[0061] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0062] In another aspect of the present invention, the present invention provides a lithium ion battery. According to an embodiment of the present invention, the lithium ion battery comprises the positive electrode sheet described above. Thus, the lithium ion battery has good electrical properties such as specific capacity and cycle capacity retention rate.
[0063] According to an embodiment of the present invention, the lithium-ion battery includes, in addition to the above-mentioned positive electrode plate, a negative electrode plate, an electrolyte and a separator.
[0064] In some embodiments of the present invention, the negative electrode sheet includes a negative electrode active material, a conductive agent and a binder.
[0065] In some embodiments, the negative electrode active material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate, among which the silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon complexes, silicon-nitrogen complexes and silicon alloys, and the tin-based material can be selected from at least one of elemental tin, tin oxide compounds and tin alloys.
[0066] In some embodiments, the conductive agent includes but is not limited to at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0067] In some embodiments, the binder includes butadiene styrene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and at least one of carboxymethyl chitosan (CMCS).
[0068] In some embodiments, the negative electrode plate may also optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0069] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0070] In some embodiments of the present invention, there is no specific limitation on the type of electrolyte, which can be selected according to the requirements. For example, the electrolyte can be liquid, gel or all-solid.
[0071] In some embodiments, the electrolyte adopts an electrolyte. The electrolyte includes an electrolyte salt and a solvent. In some embodiments, the electrolyte salt can be selected from lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bisfluorosulfonyl imide, lithium bistrifluoromethanesulfonyl imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalate borate, lithium dioxalate borate, lithium difluorobisoxalate phosphate and lithium tetrafluorooxalate phosphate. In some embodiments, the solvent can be selected from ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, ethylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0072] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and the like.
[0073] In some embodiments of the present invention, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different, without particular limitation.
[0074] In some embodiments of the present invention, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process.
[0075] In another aspect of the present invention, the present invention provides an electric device. According to an embodiment of the present invention, the electric device comprises the lithium-ion battery described above, so that the electric device has good performance.
[0076] According to some embodiments of the present invention, the electrical equipment may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, energy storage systems, etc., but are not limited thereto.
[0077] Example
[0078] Preparation method of positive electrode active material: First, LiOH·H2O is crushed into particles of a predetermined particle size (average particle size D50) by mechanical grinding, and the crushed LiOH·H2O and hydroxide precursor are mixed uniformly at a molar ratio of 1:1.03; the mixed raw materials are loaded into a 330*330*150 (mm 3 ) in a sagger, the height of the mixed raw materials in the sagger is h (mm). The temperature is raised to 750℃ in a roller kiln and kept at this temperature for 8 hours, wherein the pressure in the sintering furnace is 15Pa, and the positive electrode active material is obtained after being crushed and refined.
[0079] The specific steps of preparing button batteries are as follows: (1) Weigh the above-mentioned positive electrode active materials, conductive acetylene black and polyvinylidene fluoride (PVDF) in a mass ratio of 95:3:2, first dissolve PVDF in an appropriate amount of N-methylpyrrolidone (NMP), then add the mixed positive electrode active materials and acetylene black powder into NMP and stir evenly to prepare positive electrode slurry; (2) Evenly apply the positive electrode slurry on an aluminum foil substrate, put the wet electrode into a vacuum drying oven, dry it at 110°C for 12 hours, and cut it into positive electrode sheets; (3) Assemble the button battery in a dry vacuum glove box.
[0080] The above-mentioned self-made positive electrode sheet was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the Celgard2500 membrane was used as the separator, and the electrolyte was 1 mol / L LiPF6 dissolved in a solvent with a volume ratio of 1:1:1 of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC). The test conditions for the cyclic electrochemical performance were 125 cycles at 2.7-4.3V and 1C rate. The parameters of the positive electrode active materials in different embodiments and the data of the electrochemical performance test are shown in Table 1.
[0081] Examples 1 to 11
[0082] The positive electrode active material in Examples 1 to 4 is LiNi 0.88 Co 0.09 Mn 0.03 O2, the positive electrode active material in Examples 5 to 11 is LiNi 0.904 Co 0.059 Mn 0.037 O2, and the precursor bulk density is 1.9g / cm 3 , h=97mm.
[0083] Record the average particle size D50 (actual value x1) of LiOH·H2O and the amount of sagger per unit volume (actual value z1) in production. Use formula (1) and formula (2) to calculate the amount of sagger per unit volume (theoretical value z2) based on the average particle size D50 of LiOH·H2O, and then compare it with the actual value (z1) of the amount of sagger per unit volume in production to observe the size of △z (△z=z1-z2). The production data and performance test data can be found in Table 1 and Table 2 respectively. Among them, the residual alkali content can be obtained by the test method in the national standard GB / T 41704-2022.
[0084] Table 1
[0085]
[0086] It can be seen from the data in Table 1 that △z in the above embodiments is between -0.03 and 0.03, which means that the error between the amount of sagger filled per unit volume calculated according to formula (1) and formula (2) of the present invention and the amount of sagger filled per unit volume in actual production is very small. It can be shown that the present invention can accurately predict the production capacity of the production line based on the determined lithium source particle size, which has guiding significance for actual production.
[0087] The present application further tests the positive electrode active materials obtained in Examples 1 to 4 and their XRD spectra are as follows: Figure 1As shown, it can be observed that the positive electrode active material exhibits typical structural characteristics of LiNiO2 positive electrode active material, and its diffraction peak is the characteristic peak of a-NaFeO2 layered structure, belonging to the hexagonal crystal system, R-3m space group, and the two pairs of diffraction peaks (006) / (012) and (008) / (110) are obviously split, forming a better layered structure. The diffraction peaks of the material before and after coating and doping do not change significantly, and there are no impurity peaks and similar peak structures, indicating that the structure of the polycrystalline high nickel ternary positive electrode active material with a Ni content of 0.88 prepared by lithium hydroxide with a particle size of 13.5-20μm has no obvious effect, and the product structure difference is relatively low.
[0088] Table 2
[0089]
[0090] The present application also performs electron microscopy (SEM) scanning on the positive electrode active materials obtained in Examples 1 to 4, and the electron microscopy images can be found in Figure 2 , Figure 3 , Figure 4 and Figure 5 It can be observed that the positive electrode active materials all exhibit a good spherical structure, the secondary particle size is 14-16μm, the surface morphology and structure are similar, and the degree of lithiation is similar. It can be seen that based on the limitation of right 1, when the particle size of the lithium source is 13.5-50μm, not only a higher production capacity can be obtained, but also the material difference is small. At the same time, combined with Table 1 and Table 2, it can be seen that within this range, the residual alkali content on the surface of the positive electrode material is close, and the electrical properties are close. Therefore, the preparation method described in this application can achieve the consistency of the performance of the positive electrode active material prepared in a specific LiOH particle size range.
[0091] At the same time, the present application also carried out Examples 6 to 11, and selected a lithium source particle size of 13.5-400 μm to prepare a polycrystalline high-nickel ternary positive electrode active material with a Ni content of 0.904 for verification. The positive electrode active materials obtained in Examples 6 to 11 were respectively subjected to electron microscopy scanning (SEM). The electron microscopy images can be seen in Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 and Fig.11 It can be observed that the positive electrode active materials prepared with a diameter of 50 μm and above have particles that have not been lithiated ( Fig. 9 , Fig.10 and Fig.11Particles pointed out by the arrow in the middle), and particles will be broken when the particle size is 400μm. Further combination of Table 1 and Table 2 shows that when the lithium source particle size is greater than 50μm, the residual alkali content jumps, especially when the lithium source particle size is greater than 100μm, the electrical performance decreases. Therefore, based on the formula of this application, the theoretical production capacity corresponding to different particle sizes can be obtained. The difference between the theoretical production capacity and the actual production capacity is small, the accuracy is very high, and it has practical guiding significance. Among them, when the lithium source particle size is limited to 13.5-50μm, it can have both production capacity and good electrical properties, especially when the particle size is 13.5-25μm, the prepared positive electrode active material has good performance consistency.
[0092] In summary, the preparation method defined in this application has excellent guiding significance for the production of positive electrode active materials. The relationship between the average particle size D50 of LiOH·H2O, the bulk density of the mixed raw materials, and the amount of sagger per unit volume can be established in the production process, and the production capacity of the production line can be accurately controlled by controlling the particle size of the lithium source. Moreover, when the average particle size D50 of LiOH·H2O is between 13.5 and 50 microns, the battery performance is optimal, and formula (1) and formula (2) have better guiding significance for actual production.
[0093] Example 12, Comparative Example 1-2
[0094] The positive electrode active material in Example 12 is LiNi0.904Co0.059Mn0.037O2, and the precursor bulk density is 1.9g / cm3, h=97mm. The average particle size D50 (theoretical value x2) of LiOH·H2O is calculated according to formula (1) and formula (2) by the unit volume sagger filling amount in actual production, and compared with the actual value (x1) of the average particle size D50 in actual production, the size of △x (△x=x1-x2) is observed. The production data and performance test data can be found in Tables 3 and 4.
[0095] Table 3
[0096]
[0097] Table 4
[0098]
[0099] It can be seen from the data of Example 12 that the present invention can reversely calculate the average particle size of the lithium source according to formula (1) and formula (2) through the amount of sagger filled per unit volume, △x = -0.4μm, and the difference is small, which means that the error between the average particle size of the lithium source calculated according to formula (1) and formula (2) of the present invention and the average particle size of the lithium source in actual production is very small. This can help to quickly obtain the lithium source particle size required for preparing positive electrode active materials, and still prepare positive electrode active materials with good performance.
[0100] Comparative Example 1 is a theoretical calculation value based on the formula in Example 8 (when the average particle size D 50 When the particle size is 50 μm, the theoretical bulk density y2 of the mixed raw material is 1.206 g / cm 3 , the theoretical value z2 of the amount of sagger filling per unit volume is 1.197 kg / dm3) in an actual production example, in Comparative Example 1, the lithium source used in the actual production is lithium hydroxide (x1=55 μm) with an average particle size D50 greater than 50 μm, and the actual value x1 of the amount of sagger filling per unit volume in production is 1.212 kg / dm3 by changing the bulk density of the lithium source and the precursor mixture, and △z=z1-z2 is within the range of -0.03 to 0.03, but because the average particle size D50 and the bulk density of the mixture are changed at the same time, Formulas 1 and 2 are not satisfied. It can be seen from the data in Tables 3 and 4 that the electrical properties of the positive electrode material obtained in Comparative Example 1 are worse than those in Example 9;
[0101] Comparative Example 2 is also based on the theoretical calculation value of the formula in Example 8 (when the average particle size D50 is 50 μm, the theoretical bulk density y2 of the mixed raw material is 1.206 g / cm 3 , the theoretical value z2 of the amount of sagger filling per unit volume is 1.197 kg / dm3) in the actual production example, in comparative example 2, the same bulk density of the lithium source and precursor mixture as in Example 8 is used for filling in the actual production, but the lithium source is changed to an average particle size D 50 The lithium hydroxide (x1 = 40 μm) is less than 50 μm. At the same time, the ratio of lithium source to precursor is adjusted or the bulk density of the precursor is increased. In actual production, it is found that when the average particle size D 50 When y2 is 40 μm, if y2 is 1.206, it is necessary to adjust the ratio of the lithium source to the precursor, specifically based on the precursor of Example 8, increase the amount of the precursor, and reduce the amount of the lithium source. The positive electrode material obtained is shown in Tables 3 and 4. Although △z=z1-z2 can be guaranteed to be within -0.03 to 0.03, because Formula 2 is not satisfied, its electrical properties will also be reduced. In summary, by comparing the two sets of data in Comparative Examples 1-2 and the data in Example 8, it can be seen that only when the particle size of the lithium source, the loose density of the mixture and the amount of the pot all meet the technical solution to be protected by this application, can both production capacity and performance be achieved, and the electrical performance data obtained are close. This can further illustrate the guiding significance of the formula of the present invention for the preparation of positive active materials.
[0102] Example 13 to Example 19
[0103] The positive electrode active material is LiNi 0.904 Co 0.059 Mn 0.037 O2.
[0104] In Examples 13 to 15, the bulk density (AD) y of the mixed raw material and the amount of material z per unit volume of the sagger were calculated by using the average particle size D50 x of LiOH·H2O according to Formula (1) and Formula (2). The positive electrode active material was produced according to the calculated bulk density (AD) y of the mixed raw material and the amount of material z per unit volume of the sagger. The calculated data and performance test data are shown in Table 5.
[0105] In Examples 16 to 19, the charging height h of the mixed raw materials in the sagger is further changed so that the relationship between h and H satisfies h=55%H~75%H, and h is less than 55%H (Example 16), and h is greater than 75%H (Example 19). The calculation data and performance test data are shown in Table 5.
[0106] Table 5
[0107]
[0108]
[0109] It can be seen from the data in Table 5 that the bulk density (AD) y of the mixed raw material and the amount of sagger per unit volume z calculated by the formula (1) and the formula (2) of the present invention are used to guide the production of positive electrode active materials. The positive electrode active materials produced still have good electrical properties and low residual alkali content. The batteries prepared therefrom also still have good specific capacity, cycle capacity retention rate and other properties. It can be seen that the formula (1) and the formula (2) of the present invention can be used to guide the production process of positive electrode active materials.
[0110] In addition, when the charging height h of the mixed raw materials in the sagger and the relationship between h and H satisfy h=55%H~75%H, it not only has a better sagger filling amount per unit volume, which helps to improve production capacity, but also can reduce the residual alkali amount of the prepared positive electrode active material. Specifically, compared with Examples 16 and 19, the sagger filling amount per unit volume of Example 16 is relatively low, and the residual alkali amount of the positive electrode active material prepared in Example 19 is relatively high.
[0111] Example 20 and Comparative Examples 3-4
[0112] The positive electrode active material is LiNi 0.904 Co 0.059 Mn 0.037 O2, h = 97 mm, the variable is the bulk density of the precursor.
[0113] The average particle size D50 (actual value x1) of LiOH·H2O, the bulk density (AD) of the mixed raw material (actual value y1) and the amount of potting per unit volume in the sagger (actual value z1) in production are recorded. The bulk density (AD) of the mixed raw material (theoretical value y2) and the amount of potting per unit volume in the sagger (theoretical value z2) are calculated according to the average particle size D50 of LiOH·H2O using formula (1) and formula (2), and then compared with the bulk density (AD) of the mixed raw material (actual value y1) and the actual value (z1) of the amount of potting per unit volume in the sagger recorded in production, and the size of Δy (Δy=y1-y2) and △z (△z=z1-z2) are observed. The production data and performance test data can be found in Table 6.
[0114] Table 6
[0115]
[0116] From the data in Table 6, it can be seen that the bulk density AD of the precursor is less than 1.7 g / cm 3 , the values of △y and △z are relatively large, and are not within the range of -0.03 to 0.03, which means that the error between the amount of sagger filled per unit volume calculated according to formula (1) and formula (2) of the present invention and the amount of sagger filled per unit volume in actual production is large, and the error between the calculated bulk density (AD) of the mixed raw material and the bulk density (AD) of the mixed raw material in actual production is large, which reduces the accuracy of the formula and makes it have no guiding significance for the production of positive electrode active materials.
[0117] In summary, the formula (1) and formula (2) of the present invention are used under the premise that the bulk density AD of the precursor is between 1.7 g / cm 3 ~2.1g / cm 3 .
[0118] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0119] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a positive electrode active material, characterized in that: include: The lithium source and the precursor are uniformly mixed to obtain a mixed raw material, and the mixed raw material is placed in a sagger, wherein the bulk density of the precursor is 1.7 g / cm 3 -2.1g / cm 3 ; The mixed raw material is sintered to obtain the positive electrode active material. The average particle size D50x (μm) of the lithium source and the bulk density y (g / cm 3 ), unit volume of sagger filling amount z (kg / dm 3 ) satisfies the following formula (1) and formula (2), y=0.77+0.12ln(x-12.28) formula (2).
2. The method according to claim 1, characterized in that The lithium source is LiOH·H2O, and the average particle size D50 of the lithium source is 13.5 μm-50 μm.
3. The method according to claim 1, characterized in that The loading height of the sagger is 55%-75% of the height of the sagger.
4. The method according to claim 1, characterized in that The height of the sagger is 135mm-165mm, and the loading height of the sagger is 90mm-100mm.
5. The method according to claim 1, characterized in that The precursor is Ni e Co b Mn c R d (OH)2, R is a doping element, the doping element is one or more of Al, Zr, Y, Mg, W, 0.6≤e≤1.0, 0.0≤b≤0.3, 0.0≤c≤0.3, 0.0≤d≤0.3, 0.95≤e+b+c+d≤1.
05.
6. The method according to claim 1, characterized in that At least one of the following conditions is also met: The molar ratio of the lithium source to the precursor is 1.0 to 1.05; The mixed raw material also includes additives; The sintering process is performed at a temperature of 650°C to 850°C and for a time of 6h to 10h; The sintering pressure is less than or equal to 20 Pa; The oxygen concentration in the sintering process is ≥90%.
7. The method according to claim 1, characterized in that The bulk density of the mixed raw materials in the sagger is greater than or equal to 0.81 g / cm 3 The amount of sagger per unit volume is greater than or equal to 0.75 kg / dm 3 .
8. A positive electrode active material, characterized in that The invention comprises a product prepared by the method according to any one of claims 1 to 7.
9. A positive electrode sheet, characterized in that: Comprising the positive electrode active material according to claim 8.
10. A lithium ion battery, characterized in that: Including the positive electrode sheet as described in claim 9.
11. An electrical device, characterized in that: Includes the lithium ion battery as claimed in claim 10.